Remarkable Effects of External Magnetic Field on Circularly Polarized Luminescence of EuIII(hfa)3 with Phosphine Chirality. Issue 17 (30th July 2021) - Mishima, Kohei; Kaji, Daiki; Fujiki, Michiya; Imai, Yoshitane
Abstract: Herein, magnetic circularly polarized luminescence (CPL) (MCPL) spectroscopy was conducted to analyze an Eu III (hfa)3 complex with three chiral P III ‐ligands. Resultantly, ( R )‐chirality luminophores with S‐up orientation and ( S )‐chirality luminophores with N‐up orientation were observed to possess symmetrical mirror image spectra, i. e., they were enantiomers. Similarly, the ( R )‐chirality luminophores with N‐up orientation and the ( S )‐chirality luminophores with S‐up orientation were also enantiomers. Contrarily, ( R )‐S‐up and ( S )‐S‐up were diastereomers and did not possess a mirror‐image relationship. Likewise, ( R )‐N‐up and ( S )‐N‐up were diastereomers. The J ‐dependency of g MCPL and g CPL datasets suggested that the N‐up/S‐up external magnetic field, with the aid of chiral P III ‐ligands, increased the g MCPL values by two‐ to sixteen‐fold and modulated the g MCPL signs at J =1–4. Additionally, the origins of the nonideal mirror‐symmetric CPL and MCPL spectral characteristics of Eu III (hfa)3 with three chiral P III ‐ligands were discussed in terms of parity (space‐inversion, P )‐symmetry, time‐reversal ( T )‐symmetry, and PT ‐symmetry laws. Abstract : Exposing a Δ / Λ mixture of Eu III (hfa)3 with chiral P III ‐ligands to north‐/south‐up magnetic fields enhanced the magnitudes of the circularly polarized light, and modulated their magnetic circularly polarized luminescence (MCPL) signs.